DEL DISCURSO A LA LEXICOGRAFÍA: PROPUESTA DE APLICACIÓN PARA LOS CONECTORES REFORMULATIVOS - Martorell, Carme Bach (Organon, 2003)
This paper aims at defending the necessity of creating applicationsfrom studies on discourse, so that applied linguistics becomes auseful tool for the society. This work explains briefly what reformulationconnectors are and it shows the electronic prototype (than can be consultedby internet) of a tool designed to make the work of lexicographerseasy concerning the entrance of connectors in the dictionaries (ALCOR),by making emphasis on the theoretical base on which it is sustained andon the decisions of application that have been taken into account.